2016
DOI: 10.1083/jcb.201510032
|View full text |Cite
|
Sign up to set email alerts
|

Defective control of pre–messenger RNA splicing in human disease

Abstract: Examples of associations between human disease and defects in pre–messenger RNA splicing/alternative splicing are accumulating. Although many alterations are caused by mutations in splicing signals or regulatory sequence elements, recent studies have noted the disruptive impact of mutated generic spliceosome components and splicing regulatory proteins. This review highlights recent progress in our understanding of how the altered splicing function of RNA-binding proteins contributes to myelodysplastic syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 175 publications
(223 reference statements)
2
162
0
1
Order By: Relevance
“…The maturation of the snRNAs in the cytoplasm consists of a series of tightly regulated, strictly ordered molecular events highlighted by the assembly of the Sm ring and hypermethylation of the m 7 G cap (Matera and Wang 2014). It has been reported that the survival of motor neuron (SMN) complex facilitates the assembly of the Sm ring complex on the Sm site [A(U) 4-6 G] of pre-snRNAs and safeguards against aberrant snRNP biogenesis and splicing-associated human syndromes, such as spinal muscular atrophy and cancers Golembe et al 2005;Matera and Wang 2014;Chabot and Shkreta 2016).…”
mentioning
confidence: 99%
“…The maturation of the snRNAs in the cytoplasm consists of a series of tightly regulated, strictly ordered molecular events highlighted by the assembly of the Sm ring and hypermethylation of the m 7 G cap (Matera and Wang 2014). It has been reported that the survival of motor neuron (SMN) complex facilitates the assembly of the Sm ring complex on the Sm site [A(U) 4-6 G] of pre-snRNAs and safeguards against aberrant snRNP biogenesis and splicing-associated human syndromes, such as spinal muscular atrophy and cancers Golembe et al 2005;Matera and Wang 2014;Chabot and Shkreta 2016).…”
mentioning
confidence: 99%
“…An important field of investigation is how dysregulation of splicing can be involved in cancerogenesis [258, 259]. Splicing defects in cancer cells can result from base-pair substitutions in splice sites or in splicing regulatory sequences.…”
Section: Formation and Export Of Mrnps Linked To Diseasementioning
confidence: 99%
“…As more than 90% of human genetic variation maps outside protein-coding regions, at inter- or intragenic sequences, and >40% maps within introns (Maurano et al, 2012), it is attractive to hypothesize that mutations at RS-sites may contribute to disease manifestation. Splicing defects are now well-established contributors in various diseases (Chabot and Shkreta, 2016), and RS, yet another layer of splicing regulation, remains unexplored. In fact, when we intersected a list of high-confidence RS-sites from human brain (Sibley et al, 2015) or endothelial cells (Kelly et al, 2015) to an ensemble of all putatively disease-causative human SNPs, they overlapped (within the 40 preceding the RS-junction) those associated with neurological (e.g., Parkinson's disease, cognitive performance) or circulatory disorders/traits (e.g., retinal vascular caliper, blood pressure), respectively, more than what was expected by chance (A. Papantonis; unpublished data).…”
Section: Regulatory and Disease Implications Of Recursive Splicingmentioning
confidence: 99%